National Identity in 21st-Century Cuban Cinema Screening the Repeating Island - Fehimović, Dunja (Springer International Publishing, 2018)
National Identity in 21st-Century Cuban Cinema tours early 21st-century Cuban cinema through four key figures-the monster, the child, the historic icon, and the recluse-in order to offer a new perspective on the relationship between the Revolution, culture, and national identity in contemporary Cuba. Exploring films chosen to convey a recent diversification of subject matters, genres, and approaches, it depicts a changing industrial landscape in which the national film institute (ICAIC) coexists with international co-producers and small, 'independent' production companies. By tracing the reappearance, reconfiguration, and recycling of national identity in recent fiction feature films, the book demonstrates that the spectre of the national haunts Cuban cinema in ways that reflect intensified transnational flows of people, capital, and culture. Moreover, it shows that the creative manifestations of this spectre screen-both hiding and revealing-a persistent anxiety around Cubanness even as national identity is transformed by connections to the outside world.